2021
DOI: 10.1038/s41598-021-84388-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dielectric permittivity of water on the shape of PtNPs synthesized in high-pressure high-temperature microwave reactor

Abstract: In this paper, a novel method for the synthesis of Pt nanoparticles (PtNPs) using a microwave autoclave reactor is proposed. For benchmarking, the obtained results are compared with the traditional, batch method. A novel process window is proposed, which is the application of high-temperature and high-pressure. The main finding is that this only brings advantage, when the ionic strength of the system is enough low. It is explained, that at high pressure and high temperature, water behaves like only a slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Magnum II has a maximum filling capacity of 108 cm 3 . Maximum microwave output power is equal to 600 W. The maximum attainable temperature is 300 • C and the maximum pressure is 50 bars [32]. In this apparatus, it is also possible to monitor the temperature and pressure during the reaction.…”
Section: Experimental and Materialsmentioning
confidence: 99%
“…Magnum II has a maximum filling capacity of 108 cm 3 . Maximum microwave output power is equal to 600 W. The maximum attainable temperature is 300 • C and the maximum pressure is 50 bars [32]. In this apparatus, it is also possible to monitor the temperature and pressure during the reaction.…”
Section: Experimental and Materialsmentioning
confidence: 99%
“…When the reduction is conducted under atmospheric pressure, the boiling point of the reaction mixture defines the upper limit of temperature and, thus, the reaction rate. This is common to reduce noble metal complexes at a high temperature [58,59]. Higher reduction rates can be achieved at temperatures above the boiling point of the reaction mixture, but the process must be conducted in a pressurized vessel.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in shape is only due to the use of different solvents for ODA. Wojnicki et al [47] describe the influence of the dielectric permittivity of water on the shape of PtNPs obtained during chemical synthesis. Authors suggested that the adsorption of TSC (playing as a stabilizing agent) at the surface of PtNPs depends on dielectric constants.…”
Section: Hr-tem Analysismentioning
confidence: 99%